Sense of coherence and life satisfaction among Jordanian university students - Abu Khadra, Farah; Aburub, Aseel; Amro, Anwaar; Csapek, Zoltán; Kertai, Bendeguz; Jeges, Sára; Tóth, Ákos Levente (Journal of International Students, 2025)
This study examines university students' life satisfaction, well-being, and sense of coherence. It focuses on Jordanian students studying in Jordan and those studying abroad in Hungary by using the Optimal Living Profile-Modified, evaluating well-being and life satisfaction, and the Sense of Coherence, measuring comprehensibility, manageability, and meaningfulness. Data from 307 students revealed that while demographics affect SOC, the role of cultural context was significant. Jordanian students studying in Hungary reported stronger meaningfulness, highlighting the impact of international students' experiences. Emotional and social health dimensions were predictors of life satisfaction, with SOC indirectly influencing life satisfaction through the emotional health dimension. This study contributes to understanding how SOC can shape well-being among university students locally or abroad, offering insights into interventions for enhancing student well-being in higher education.